INTESTINAL MORPHOLOGY OF NATIVE CHICKENS AT 20 WEEKS-OLD SUPPLEMENTED BY DL-METHIONINE AND L-LYSINE HCL INTO FEED - Lisnahan, Charles V; Wihandoyo, Wihandoyo; Zuprizal, Zuprizal; Harimurti, Sri (Journal of Tropical Animal Science and Technology, 2019)
The aim of this study was to determine the effect of the supplementation of dl-methionine and l-lysine HCl into feed based on cafeteria standards to intestinal morphology of native chickens at 20 weeks-old. A total of 128 fourteen week-old native chickens were used in this study. The native chickens were divided into 4 treatments groups with 4 replications. The dietary treatments were: T0 (feed based on cafeteria standard), T1 (feed based on protein standard of NRC), T2 (cafeteria feed+0.09% dl-methionine+0.22% l-lysine HCl), T3 (cafeteria feed+0.19% dl-methionine+0.42% l-lysine HCl). The data collected were villus height, crypt depth and villus width of duodenum, jejunum and ileum of native chickens aged 20 weeks. The result of this study for T0, T1, T2 and T3 showed that villus height of duodenum were 863.03; 1237.85; 1171.60 and 1261.15 µm, crypt depth 212.70; 192.08; 210.25 and 251.85 µm, villus width 168.74; 168.53; 213.61 and 188.60 µm. Villus height of jejunum were 1381.48; 1088.70; 1072.68 and 1383.15 µm, crypt depth 272.,05; 261.83; 225.00 and 205.65 µm, villus width 188.28; 166.41; 216.26 and 182.95 µm. villus height of ileum were 798.03; 863.35; 882.88 and 828.70 µm, crypt depth 199.58; 199.58; 154.68 and 145.78 µm and villus width 181.13; 154.55; 201.25 dan 175.65 µm, respectively. It can be concluded that supplementation of dl-methionine and l-lysine HCl was not effected upon villus height, crypt depth and villus width of duodenum, jejunum and ileum of native chickens aged 20 weeks.